Seventy-three years (1951-2024) looking for trigeminal neuralgia therapy and peripheral nerve stimulation as a niche theme [version 1; peer review: awaiting peer review] - SALEH, ARMAN YURISALDI; Valentina, Riezky; Saputra, Dwi Arwandi Yogi (F1000 research, 2024)
Introduction Trigeminal neuralgia (TN) is a severe condition that causes severe pain and emotional distress in the brain. It can significantly impact the quality of a person's life and lead to daily withdrawal and emotional instability. Despite extensive research, there is still a need for comprehensive bibliometric studies to understand the literature on TN. This study is particularly important as there are no existing bibliometric studies on TN on Scopus, providing new opportunities for research and innovation in TN treatment. Methods In this work, a literature review methodology is employed to gather data from the Scopus database using the keywords "trigeminal neuralgia", current and therapy. Data were analyzed using Biblioshiny and VOSviewer software to produce visualizations and bibliometric maps. We conducted quantitative and qualitative analysis Results The research trend found are documents by year, most global cited document, most relevant sources, factorial map of the documents with the highest contributes, documents by author, documents by country or territory, documents by affiliation, documents by subject area, network visualization, overlay visualization of scopus database using vosviewer, density visualization, thematic map, thematic evolution, cluster analysis, and qualitative analysis. Conclusions The study focuses on trigeminal neuralgia, a topic of research and a recent topic involving periferal nerve stimulation and the use of karbamazepin, a new topic in the field of therapy.